Organizational Interventions to Support Second Victims in Acute Care Settings: A Scoping Study. Issue 1 (13th January 2022) - Wade, Laura; Fitzpatrick, Eleanor; Williams, Natalie; Parker, Robin; Hurley, Katrina F.
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: Health care providers that experience harm after adverse events have been termed "second victims." Our objective was to characterize the range and context of interventions to support second victims in acute care settings. Methods: We performed a scoping study using Arksey and O'Malley's process. A library scientist searched PubMed, Cumulative Index of Nursing and Allied Health, EMBASE, and Cochrane Central Register of Controlled Trials in September 2017, and updated the search in November 2018. We sought gray literature (Canadian Electronic Library, Proquest and Scopus) and searched reference lists of included studies. Stakeholder organizations and authors of included studies were contacted. Two reviewers independently reviewed titles and abstracts and extracted data. A qualitative approach was used to categorize the context and characteristics of the 22 identified interventions. Results: After screening 5634 titles and abstracts, 173 articles underwent full-text screening. Twenty-two interventions met the criteria and were categorized as providing peer support (n = 8), proactive education (n = 6), or both (n = 8). Programs came from Canada (n = 2), Spain (n = 2), and the United States (n = 18). A specific traumatic event triggered the development of 5 programs. Some programs used a standard definition of second victims, (n = 6), whereas other programs had a broader scope (n = 12). Confidentiality was explicitly assured in 9 peer support programs. Outcome measures were often not reported. Conclusions: This is a new area of study with little qualitative data from which to determine whether these programs are effective. Many programs had a similar design, based on the structure proposed by the same small group of experts in this new field. Concerns about potential legal proceedings hinder documentation and study of program effectiveness.